Analysis of rate of force development as a vertical jump height predictor - Miller, J. D.; Fry, A. C.; Ciccone, A. B.; Poggio, J. (Research Quarterly for Exercise and Sport, 2023)
Purpose Many researchers and coaches hold that the ability to generate force rapidly is an important factor in athletic performance. This concept is often studied by analyzing the rate of ground reaction force development (RFD) during vertical jumps; however, many such studies disagree on whether estimates of RFD are true predictors of vertical jump height, have limited sample sizes, and have not employed multiple regression analysis. Therefore, the purpose of the study was to assess the utility of RFD as a predictor of vertical jump height.